Bianchi type-I cosmological models in Schwinger's scalar tensor theory - Singh T. (My University, 2025)
Cosmological equations for a Bianchi type-I empty universe are solved in the scalar tensor theory proposed by Schwinger and the behaviour of the model is discussed. © 1984 Società Italiana di Fisica.